Design of Ge/GeSi quantum well infrared photodetector - Xu, Yifei (2016)
The intention of the current project was the designing of a 9um quantum well-infrared photodetector using Ge/GeSi. There were some assumptions made for the calculations. Only the single band Hamiltonian Operator was used, instead of the multi-band Hamiltonian Operator. Many body effects were also not considered. The protocol of interest focused on the attaining adjustment on key elements of the quantum well. They included the fixing of the well width and the subsequent adjustment of the barrier width, fixing of barrier width and the subsequent adjustment of well width. Both widths were essential in the evaluation of the modelled photodetector. It was established through PL and XRD measurements when the Ge and Si compositions are Ge/Ge0.986Si0.014, Ge/Ge0.972Si0.028, Ge/Ge0.958Si0.042 and Ge/Ge0.944Si0.056. Based on calculations and simulations, compare the intersubband energy levels and absorption at 9 μm wavelength. Upon engaging a chary analysing from the simulated graphs and data, a conclusion on the possible attainment of the desired readings was achieved. It focused on the realization of the 9um wavelength of Ge/GeSi quantum well, provided that Ge/GeSi be considered adjustable in the implementation of the measurement process. It was established that there arose a need to try growing the material of QWIP in the hope of developing further precision potential.